Penerapan buku kas pada UMKM Bojonegoro - Andika Putra; Fitriana Santi (University of Merdeka Malang, 2020)
This study aims to apply accounting records in the form of a cash book at Bojonegoro SMEs. MSMEs are one of the businesses that have an important role in providing jobs for the unemployed. The independence of MSMEs in running a business is the reason for the government to focus on this business. However, it is unfortunate that many business people do not have the knowledge in recording business transactions. This study uses a qualitative method. Determination of informants with purposive sampling technique. The results of the study show that MSME actors can apply a simple cash book so that it can help them find out the company's balance.